Content Analysis of the Nature of Science in the Thematic Learning Book for Lower Grade Elementary School 2013 Curriculum - Suryani, Rani; Widodo, Ari (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The main book used in learning in elementary schools from upper to lower grades is currently the 2013 Curriculum thematic learning book. This study aims to describe the level of Nature of Science (NOS) content in the lower grade thematic curriculum books. This research is a descriptive research with the object of research being a thematic learning book for elementary school students in the lower grades of the 2013 curriculum, namely grades 1-3. Data was collected through observation techniques using research instruments that included an analysis of NOS aspects. After collecting the data, it was analyzed by grouping and scoring, as well as being tested for validity and reliability, before being described and drawing conclusions. The results showed that the level of NOS content in the thematic learning materials for lower grade elementary school students in the 2013 curriculum was very low, namely 3.7%. So it can be said that the NOS aspect in the lower grade 2013 curriculum books has not appeared.